Neonatal mortality risk of vulnerable newborns by fine stratum of gestational age and birthweight for 230 679 live births in nine low- and middle-income countries, 2000-2017 - Hazel, Elizabeth A.; Erchick, Daniel J.; Katz, Joanne; Lee, Anne C. C.; Diaz, Michael; Wu, Lee S. F.; West, Keith P.; Shamim, Abu Ahmed; Christian, Parul; Ali, Hasmot; Baqui, Abdullah H.; Saha, Samir K.; et al. (Wiley, 2025)
To describe the mortality risks by fine strata of gestational age and birthweight among 230 679 live births in nine low‐ and middle‐income countries (LMICs) from 2000 to 2017.Descriptive multi‐country secondary data analysis.Nine LMICs in sub‐Saharan Africa, Southern and Eastern Asia, and Latin America.Liveborn infants from 15 population‐based cohorts.Subnational, population‐based studies with high‐quality birth outcome data were invited to join the Vulnerable Newborn Measurement Collaboration. All studies included birthweight, gestational age measured by ultrasound or last menstrual period, infant sex and neonatal survival. We defined adequate birthweight as 2500–3999 g (reference category), macrosomia as ≥4000 g, moderate low as 1500–2499 g and very low birthweight as <1500 g. We analysed fine strata classifications of preterm, term and post‐term: ≥42+0, 39+0–41+6 (reference category), 37+0–38+6, 34+0–36+6,34+0–36+6,32+0–33+6, 30+0–31+6, 28+0–29+6 and less than 28 weeks.Median and interquartile ranges by study for neonatal mortality rates (NMR) and relative risks (RR). We also performed meta‐analysis for the relative mortality risks with 95% confidence intervals (CIs) by the fine categories, stratified by regional study setting (sub‐Saharan Africa and Southern Asia) and study‐level NMR (≤25 versus >25 neonatal deaths per 1000 live births).We found a dose–response relationship between lower gestational ages and birthweights with increasing neonatal mortality risks. The highest NMR and RR were among preterm babies born at <28 weeks (median NMR 359.2 per 1000 live births; RR 18.0, 95% CI 8.6–37.6) and very low birthweight (462.8 per 1000 live births; RR 43.4, 95% CI 29.5–63.9). We found no statistically significant neonatal mortality risk for macrosomia (RR 1.1, 95% CI 0.6–3.0) but a statistically significant risk for all preterm babies, post‐term babies (RR 1.3, 95% CI 1.1–1.5) and babies born at 370–386 weeks (RR 1.2, 95% CI 1.0–1.4). There were no statistically significant differences by region or underlying neonatal mortality.In addition to tracking vulnerable newborn types, monitoring finer categories of birthweight and gestational age will allow for better understanding of the predictors, interventions and health outcomes for vulnerable newborns. It is imperative that all newborns from live births and stillbirths have an accurate recorded weight and gestational age to track maternal and neonatal health and optimise prevention and care of vulnerable newborns.